Guided Self-rehabilitation Contracts Combined With AbobotulinumtoxinA in Adults With Spastic Paresis. Issue 3 (July 2021) - Gracies, Jean-Michel; Francisco, Gerard E.; Jech, Robert; Khatkova, Svetlana; Rios, Carl D.; Maisonobe, Pascal
Abstract : Background and Purpose: Guided self-rehabilitation contracts (GSCs) are a diary-based rehabilitation strategy, wherein specific muscles are identified for prescription of high-load, home self-stretching techniques. We assessed the effect of GSCs combined with simultaneous upper limb (UL) and lower limb (LL) abobotulinumtoxinA injections on composite active range of motion (CXA ) in adults with chronic spastic paresis. Methods: This was an international, prospective, single-arm, open-label study (ENGAGE, NCT02969356). Personalized GSCs were monitored by phone every other week, alongside 2 consecutive abobotulinumtoxinA injections (1500 U) across UL and LL, over 6 to 9 months. Primary outcomes were responder rates (CXA improvement ≥35° [UL] or ≥5° [LL]) at week 6 cycle 2. Secondary outcomes were active function (UL: Modified Frenchay Scale [MFS]; LL: 10-m barefoot maximal walking speed [WS]) and quality of life (12-item Short Form Health Survey, SF-12). Results: Of the 153 treated participants, 136 had primary endpoint data; 72.1% (95% confidence interval [CI], 64.0-78.9) were responders. Mean (SD) CXA changes from baseline to last study visit were +49.3° (63.4) for UL and +20.1° (27.6) for LL. Mean (95% CI) changes from baseline to week 12 cycle 2 were +0.55 (0.43-0.66) in MFS, +0.12 m/s (0.09-0.15) for WS, and +4.0 (2.8-5.2) for SF-12 physical scores. In the safety population (n = 157), 49.7% of participants reported treatment-emergent adverse events (AEs); 12.1% reported 25 serious AEs. Discussion and Conclusions: GSC combined with simultaneous UL and LL abobotulinumtoxinA injections led to improvements in CXA and function in both limbs, and quality-of-life physical scores. These results suggest the beneficial effect of combined GSC and abobotulinumtoxinA therapy in the management of spastic paresis. Video Abstract available for more insight from the authors (see the Supplementary Video, available at: http://links.lww.com/JNPT/A346 ). Abstract : Supplemental Digital Content is Available in the Text.